The changes in the transcriptomic profiling of subcutaneous adipose tissue after bariatric surgery depend on the insulin resistance state - González-Plaza, Juan José; Santiago-Fernández, Concepción; Gutiérrez-Repiso, Carolina; García-Serrano, Sara; Rodriguez-Pacheco, Francisca; Ho-Plagaro, Ailec; Garrido-Sánchez, Lourdes; Moreno-Ruiz, Francisco J.; Rodríguez-Cañete, Alberto; García-Fuentes, Eduardo (Surgery for obesity and related diseases, 2018)
The changes that are produced in the gene expression of subcutaneous adipose tissue after Roux-en-Y gastric bypass are not yet fully known. To identify the changes in the subcutaneous adipose tissue gene expression of morbidly obese women with low insulin resistance (MO-low-IR) and high insulin resistance (MO-high-IR) to find a relationship with measured obesity-related co-morbidities. A university hospital. Subcutaneous adipose tissue samples were assessed by microarray analysis before and 2 years after Roux-en-Y gastric bypass in MO-low-IR and MO-high-IR patients. There is a group of shared differentially expressed genes (DEG) in both MO-low-IR and MO-high-IR, also there is a group of exclusive DEG in MO-low-IR and another group in MO-high-IR. In MO-high-IR, the downexpressed DEG are related to the regulation of transcription and are involved in the pathways related to cytokine-cytokine receptor interaction, cancer, phosphatidylinositol 3-kinase-protein kinase B signaling, human T-lymphotropic virus I infection, chemokine signaling, and Janus kinase/signal transducers and activators of transcription signaling. In MO-low-IR, the overexpressed DEG are related to carbohydrate metabolic processes, the downexpressed DEG to the glycosaminoglycan metabolic process and regulation of translation, and the pathways are related to phosphatidylinositol 3-kinase-protein kinase B signaling and metabolic pathways. The fold change of DEG mainly correlates with the percentage of change (Δ) of waist, Δhip, Δglucose, and Δtriglycerides. These DEG were mainly related to cancer, inflammation/immune regulation, metabolic pathways, ribonucleic acid/deoxyribonucleic acid regulation, virus infection, and regulation of cellular proliferation. This study suggests a potential association between high insulin resistance and the expression of genes related to cancer and chronic immune activation/inflammation.